The role of paternal and maternal warmth and hostility on daughter’s psychosocial outcomes: The insidious effects of father warmth combined with high paternal hostility - Dmitrieva, Julia; Espel, Emma V. (Frontiers in Psychology, 2023)
Despite the well-accepted view on the importance of parental warmth and parental hostility for adolescent development, few studies have examined the joint interactive effects of these two key aspects of parenting. Furthermore, research comparing maternal and paternal parenting is limited, with the father-daughter relationship during adolescence remaining one of the more understudied familial contexts. Given that family processes are key for the intergenerational transmission of inequality, these parent-child relationships may be especially important for youth at risk for exposure to violence. Using a sample of juvenile female offenders, this study examined the associations between the perceived warmth and hostility in the father-daughter and mother-daughter relationships on daughters’ depressive symptoms, anxiety symptoms, romantic partner warmth, romantic partner hostility, and the daughter’s sense of agency. We hypothesized that high perceived parental warmth would moderate the effects of parental hostility by protecting daughters from the negative effects of parental hostility, with stronger effects for the father-daughter than the mother-daughter relationship. In contrast, our paternal relationship findings across four of the five outcomes suggest a moderation in the opposite direction – that is, high perceived father warmth exacerbates the deleterious effects of father hostility on daughters’ depressive symptoms, anxiety, romantic partner warmth, and romantic partner hostility. Maternal warmth, and not hostility, had a direct association with these four outcomes, with stronger explanatory power shown for the father-daughter than the mother-daughter model. Higher agency was associated with maternal hostility only. Our findings suggest that daughters might be modeling and internalizing the relationship with their fathers (for better or worse) when they perceive it as warm and supportive. Consequently, adolescent girls whose fathers exhibit hostile behavior may benefit from emotional distancing from their fathers.